Deinstitutionalization of Individuals with Schizophrenia in Indonesia: A Scoping Review of Rehabilitative Interventions and Implications for Reforming Institutional Care - Nurjanah, Siti; Keliat, Budi Anna; Susanti, Herni; Susanti, Yossie Eka Putri (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Background: Deinstitutionalization is a critical component of mental health reform in Indonesia, where individuals with schizophrenia continue to be confined in long-term psychiatric facilities and subjected to practices such as pasung (physical restraint). Despite national policies promoting community-based care, the implementation of rehabilitative interventions remains fragmented.Objective: This scoping review aimed to map the landscape of rehabilitative interventions that support the deinstitutionalization of adults diagnosed with schizophrenia in Indonesia and to explore their implications for reforming institutional mental health care.Methods: A systematic literature search was conducted across PubMed, ScienceDirect, Springer, and Google Scholar for studies published between 2002 and 2024. Eligible studies included randomized controlled trials, quasi-experimental studies, longitudinal evaluations, and qualitative reports focusing on adults (≥18 years) with schizophrenia transitioning from long-term institutional settings. The search strategy followed the PRISMA 2020 and PCC (Population–Concept–Context) frameworks. Data were extracted and thematically synthesized to identify intervention types, implementation contexts, and outcome trends.Results: Fifteen studies were included. Three main intervention types emerged: community-based rehabilitation (CBR), pasung release and reintegration programs, and family-centered psychoeducation. CBR interventions demonstrated significant improvements in quality of life, social functioning, and symptom management. Pasung release programs were effective when paired with sustained psychosocial support. Family-based interventions, including task-shifting models, facilitated recovery and reduced relapse. Key enablers included strong familial involvement and decentralized health worker engagement, while barriers included persistent stigma, weak infrastructure, and policy enforcement gaps.Conclusions: Rehabilitative interventions grounded in community participation and family support show promise in advancing deinstitutionalization in Indonesia. Integration of these models into primary care, supported by policy implementation and resource allocation, is essential for sustainable reform. Future research should focus on randomized trials, cost-effectiveness analysis, and multi-provincial implementation studies to inform national mental health strategies.